4G network perception planning method based on Monte-Carlo simulation - Xiaoguang HUANG; Junhua DONG; Feng WANG; Wei WANG (Dianxin kexue)
Based on the research results of Monte-Carlo simulation technology,the service-aware air port rate guarantee threshold was established.Based on the research of Monte-Carlo simulation technology,the design method of user distribution model and business model in perceptive simulation planning was obtained,and on the basis of this,the specific simulation planning analysis ideas was given.Taking the actual planning of a certain area as an example,the method of perceived planning based on simulation was feasible and effective,and it had good promotion value by comparing the business perceived rate and service success rate before and after the planning.